Hanging force analysis for realizing low vibration of grape clusters during speedy robotic post-harvest handling - Faheem, Muhammad; Liu, Jizhan; Chang, Guozheng; Ahmad, Ibrar; Peng, Yun (International Journal of Agricultural and Biological Engineering, 2021)
Mechanical damage induced by vibration during harvesting and post-harvest handling could decrease the quality, quantity, and shelf life of the fresh grape cluster. Usually, fresh grape clusters are harvested by gripping and cutting from the main rachis in the present robotic harvesting system, then transported towards the basket during post-harvest handling. However, serious cluster vibration and corresponding berry falling may occur during the robotic transportation of hanging grape clusters. Therefore, this study was designed to perform experimental and theoretical hanging force analysis to explore the vibration mechanism of hanging grape clusters during robotic transportation. A lead screw lathe with an attached linear actuator was used to investigate the effects of four different speeds (0.4, 0.6, 0.8, 1.0 m/s) with four acceleration levels (6, 8, 10, 12 m/s2) on the vibration of the hanging grape cluster. By the experiments, the peak hanging force of the grape cluster at the start, constant speed, and stop phase of the actuator was recorded using a single axis force sensor, and the cluster’s swing angle was measured with a digital camera. The experimental results showed a linear relationship between the swing angle and hanging force of the cluster at the start and stop phase of the actuator. The multi-stage cluster’s vibration during robotic transportation was observed, and the behavior of cycled damping after a sudden stop of the actuator was found. The simulated results of hanging force of grape cluster in damping phase were agreed with experimental results with R2 more than 0.90 at an optimum acceleration of 10 m/s2. To conclude, this research provides theoretical basics for understanding the complex vibration mechanism of the hanging cluster fruits during speedy robotic transportation operations with low-loss of berry drop both on industrial and farm levels.Keywords: grape cluster, vibration mechanism, hanging force, force sensor, robotic transportation, robotic handlingDOI: 10.25165/j.ijabe.20211404.6406Citation: Faheem M, Liu J Z, Chang G Z, Ahmad I, Peng Y. Hanging force analysis for realizing low vibration of grape clusters during speedy robotic post-harvest handling. Int J Agric & Biol Eng, 2021; 14(4): 62–71.